Growth or Decline: Christian Virtues and Artificial Moral Advisors - Xu, Ximian (Studies in Christian ethics, 2025)
Artificial Intelligence (AI) has permeated every section of human life. Some even suggest that artificial moral advisors (AMAs)—that is, AI-driven artefacts designed to assist human moral growth by providing moral advice—can help humans to lead virtuous lives. With a focus on Thomas Aquinas's theological virtue ethics, this article will argue that AMA projects are cast into question because, theologically speaking, the cultivation of virtues and moral growth are inseparable from hope and patience given through God's grace, which is immeasurable and cannot be reductively mathematised into AI models. Moreover, the tension between AI's efficiency and patient moral life offers further criticism of AMAs. That said, the theology of patience brings forth a conceptual apparatus through which to qualify the virtuous AMA as a tool to bring together human moral advisors as silent hearers and human moral advisees as patient inquirers.